Building the case for embedding global health security into universal health coverage: a proposal for a unified health system that includes public health. Issue 10156 (20th October 2018) - Erondu, Ngozi A; Martin, Jerry; Marten, Robert; Ooms, Gorik; Yates, Robert; Heymann, David L
Summary: In the wake of the recent west African Ebola epidemic, there is global consensus on the need for strong health systems; however, agreement is less apparent on effective mechanisms for establishing and maintaining these systems, particularly in resource-constrained settings and in the presence of multiple and sustained stresses (eg, conflict, famine, climate change, and globalisation). The construction of the International Health Regulations (2005) guidelines and the WHO health systems framework, has resulted in the separation of public health functions and health-care services, which are interdependent in actuality and must be integrated to ensure a continuous, unbroken national health system. By analysing efforts to strengthen health systems towards attaining universal health coverage and investments to improve global health security, we examine areas of overlap and offer recommendations for construction of a unified national health system that includes public health. One way towards achieving universal health coverage is to broaden the definition of a health system.